Legal Protection for Child Victims of Cyberbullying on Social Media According to the Ite Law and the Child Protection Law Case Study Number 71/PID.SUS/2023/PN PDL (ITE) - Albaiti, Maemunah Syarifah; Guntara, Peter; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Social media in the digital era is like a double-edged sword: on one side, it facilitates communication, but on the other, it can cause harm, particularly when children become victims of cyberbullying. This research focuses on Legal Protection for Children Victims of Cyberbullying on Social Media based on Law No. 19 of 2016 concerning Electronic Information and Transactions (EIT Law) and the Child Protection Law, with a case study of Court Decision No. 71/Pid.Sus/2023/PN Pdl. The background of this study lies in the increasing number of cyberbullying cases that result in serious psychological impacts, such as depression and decreased academic motivation.The objective of this research is to describe the forms of legal protection provided under both laws and to examine their implementation in the verdict of the Pandeglang District Court. The methodology employed is normative and empirical juridical research, involving literature review, analysis of statutory regulations, and examination of related court decisions. The findings indicate two types of legal protection. Preventive protection is carried out through digital education and legal literacy, while repressive protection is implemented through law enforcement as stipulated in Article 27 paragraph (3) of the EIT Law and Articles 59 and 76C of the Child Protection Law. However, its implementation still encounters obstacles, particularly in the process of evidence and the lack of psychological rehabilitation for victims. In conclusion, although the legal framework already exists, the effectiveness of legal protection for children who are victims of cyberbullying remains limited. Optimization is required through collaboration among law enforcement, the enhancement of digital education, and the strengthening of social empathy. After all, in today’s world, “a single mistyped finger can land you in court faster than in a thesis revision session.”